PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN LEMBAR KERJA SISWA (LKS) TERHADAP PENCAPAIAN KOMPETENSI BELAJAR BIOLOGI SISWA KELAS VIII DI SMP NEGERI 6 SUNGAI PENUH - Eriza, Deni Septia; Ananda, Azwir; Ahda, Yuni (Kolaboratif, 2015)
The problems encountered in this study were lack of student motivation, students have difficulty understanding the subject matter, initial cavability students are not considered, and learning competence was still low. One of the effort made to evercome this problem is by applying discovery learning model assisted with student worksheet.The purpose of this research was to reveal the effect of using discovery learning model assisted with student worksheet on the students learning competence in biology. This was a quasi experimental research, the sample of the research was the students in class VIII2 as the experimental class and VIII5 class as the control class. The experimental class was treated by discovery learning model assisted with student worksheet and the control one was taught by using conventional learning. The data was collected through a test to measure the students cognitive competence and an observation sheet to see their affective and psychomotor competences. The data obtained was analyzed by using t-test, two ways anava test and Mann Whitney U test. Based on the result of data analysis it was figured out that the learning competence on cognitive, affective and psychomotor aspects of the students taught by using discovery learning model assisted with student worksheet was better than that taught by using conventional model; learning competence on cognitive aspect of the students having high previous knowledge taught by using discovery learning model assisted with student worksheet was better than that taught by using conventional model; and there were no interaction between learning model and previous knowledge in affecting the students learning competence on cognitive aspect.